IMPLEMENTASI BELAJAR MEMBACA (BABACA) MENGGUNAKAN MEDIA PUZZLE KATA DI KELAS 2 SDN 51 CAKRANEGARA - Alfian Qori Irsandi (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2024)
One of the skills students must have is reading skills. Even so, there are still many students who have not mastered this skill. Of the 29 2nd graders, only 11 have read well. This is the basis for researchers to provide reading tutoring through the BABACA program. In its implementation, researchers also use media such as word puzzles as an attraction in learning to read. The research method used is qualitative descriptive. Based on the BABACA program and the use of word puzzle media that has been carried out, the results were found in the form of the development of students' reading skills. Of the five students who received guidance, there was only one student who did not have the progress of developing their abilities. Word puzzle media also has a positive impact on its utilisation. Students look happy and excited to break the letter arrangement of the words mentioned by the teacher.